2017
DOI: 10.4067/s0370-41062017000300013
|View full text |Cite
|
Sign up to set email alerts
|

Papilomatosis respiratoria recurrente en paciente pediátrico: reporte de un caso

Abstract: Introduction: Genetic variability related to the host immune system has been proposed as one of the most influential factors in the development of diseases caused by HPV. Clinical case: We report the case of a 5-year-old child in whom chronic laryngeal papillomatosis, probably acquired vertically during labor, was detected. The diagnosis of laryngeal papillomatosis was confirmed with a biopsy after a first surgery to remove the papillomas. The Derkay classification system was used to assess the severity of pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Available literatures have shown diverse results in terms of sex predilection in RRP. Most studies have concluded Juvenile Onset RRP to affect males and females in equal predominance but the Adult Onset RRP affects males than females [1][2][3][4]. A different picture is depicted in the adult form of RRP where males are more affected than females.…”
Section: Sex Distribution Of Recurrent Respiratory Papillomatosismentioning
confidence: 99%
See 1 more Smart Citation
“…Available literatures have shown diverse results in terms of sex predilection in RRP. Most studies have concluded Juvenile Onset RRP to affect males and females in equal predominance but the Adult Onset RRP affects males than females [1][2][3][4]. A different picture is depicted in the adult form of RRP where males are more affected than females.…”
Section: Sex Distribution Of Recurrent Respiratory Papillomatosismentioning
confidence: 99%
“…Recurrent Respiratory Papillomatosis is a rare disease characterized by recurrent growth of benign papillomatous lesions in the respiratory tree of both adults and children with the exclusive aetiology being Human papillomavirus [1][2][3][4]. Such lesions may occur anywhere in the upper aerodigestive tract [5] though in most occasions affect the larynx and that's why some literatures describe such disease condition to be "Recurrent laryngeal papillomatosis".…”
Section: Introductionmentioning
confidence: 99%